2013
DOI: 10.1016/j.pscychresns.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prospective neurochemical characterization of child offspring of parents with bipolar disorder

Abstract: We wished to determine whether decreases in N-acetyl aspartate (NAA) and increases in myoinositol (mI) concentrations as a ratio of creatine (Cr) occurred in the dorsolateral prefrontal cortex (DLPFC) of pediatric offspring of parents with bipolar disorder (BD) and a healthy comparison group (HC) over a 5 year period using proton magnetic resonance spectroscopy (1H-MRS). Sixty-four youth (9–18 years old) of parents with BD (36 with established BD, and 28 offspring with symptoms subsyndromal to mania) and 28 HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The value of these post hoc analyses rely on the ability to further investigate brain neurochemistry as a function of “pure” familial risk for bipolar disorder, as no differences were found between at‐risk youth without psychopathology and HC. Indeed, regarding the ACC, these negative results are consistent with smaller prior studies in at‐risk youth, further suggesting that, at‐risk status, per se, is not associated with abnormal 1 H‐MRS neurochemistry profile in the bilateral VLPFC and ACC.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The value of these post hoc analyses rely on the ability to further investigate brain neurochemistry as a function of “pure” familial risk for bipolar disorder, as no differences were found between at‐risk youth without psychopathology and HC. Indeed, regarding the ACC, these negative results are consistent with smaller prior studies in at‐risk youth, further suggesting that, at‐risk status, per se, is not associated with abnormal 1 H‐MRS neurochemistry profile in the bilateral VLPFC and ACC.…”
Section: Discussionsupporting
confidence: 87%
“…To date, very few 1 H‐MRS studies have examined baseline abnormalities and longitudinal changes in prefrontal cortex neurochemistry in youth at increased risk for bipolar I disorder. Prior to our study, only one 1 H‐MRS study have examined brain neurochemistry in the bilateral dorsolateral prefrontal cortex of at‐risk youth in a prospective fashion, which also yielded negative results . Different from our study, they included at‐risk youth with established bipolar disorder (therefore, after their first mood episode), or with subthreshold mania (therefore, medicated sample or with more severe psychopathology).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An MRS study of BD subjects showed significantly lower adenosine diphosphate concentrations in the ventrolateral prefrontal cortex of euthymic subjects [140]. A prospective MRS study of offspring of parents with BD found a trend towards increased myo-inositol/Cr concentrations in the dorsolateral prefrontal cortex compared to controls [141]. Another study has shown reduced expression of Na-K-ATPase in response to ethacrynic acid ionic stress challenges in lymphoblastoid cell lines of Old Order Amish BD subjects compared to control subjects within the same Amish pedigree [142].…”
Section: The Phenome Of Bd From the Ion Channel Perspectivementioning
confidence: 99%